Behavior of Reinforced Concrete Continuous Beams under Pure Torsion - Saad Khalaf Mohaisen, Ass. Prof. Dr.; Ali Adel Abdulhameed, Ass. Lect.; Majid Mohammad Kharnoob, Dr (Journal of Engineering, 2016)
Practically, torsion is normally combined with flexure and shear actions. Even though, the behavior of reinforced concrete continuous beams under pure torsion is investigated in this study. It was performed on four RC continuous beams under pure torsion. In order to produce torsional moment on the external supports, an eccentric load was applied at various distances from the longitudinal axis of the RC beams until failure.